2017
DOI: 10.1515/aoa-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Comparative Study of DAB+ Broadcast System

Abstract: Broadcasting services seek to optimize their use of bandwidth in order to maximize user's quality of experience. They aim to transmit high-quality digital speech and music signals at the lowest bitrate. They intend to offer the best quality under available conditions. Due to bandwidth limitations, audio quality is in conflict with the number of transmitted radio programs. This paper analyzes whether the quality of real-time digital DAB+ broadcasted radio programs surpasses the quality offered by analog FM radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…is the appropriate choice and setting of the audio encoding. The goal was to ensure efficient operation while keeping a high subjectively perceived sound quality [17], [18]. The assumptions were verified by blind listening tests.…”
Section: Dab+ Headend Configurationmentioning
confidence: 99%
“…is the appropriate choice and setting of the audio encoding. The goal was to ensure efficient operation while keeping a high subjectively perceived sound quality [17], [18]. The assumptions were verified by blind listening tests.…”
Section: Dab+ Headend Configurationmentioning
confidence: 99%
“…A subjective and objective study, concerning the comparison of real-time simulcasted FM and DAB+ radio programs in Poland, along with AAC-processed speech and music signal samples (bitrates ranging from 64 to 160 kbps, with a step of 32 kbps), is described in [25]. In this work, the authors analyzed whether the quality of DAB+ surpasses the quality of FM radio.…”
Section: Related Workmentioning
confidence: 99%
“…The observed difference ranges from 0.02 (Arts-broadcasted in DAB+ at 128 kbps) and 0.05 (Pop Musicbroadcasted in DAB+ at 128 kbps) to 0.77 (Regional PL-broadcasted in DAB+ at 112 kbps). Moreover, a comparison has been performed by considering the results published in 2017 [25], including the same group of radio programs as well as the same number of individuals, namely 45 According to obtained results, all scores favor the digital system. The observed difference ranges from 0.02 (Arts-broadcasted in DAB+ at 128 kbps) and 0.05 (Pop Musicbroadcasted in DAB+ at 128 kbps) to 0.77 (Regional PL-broadcasted in DAB+ at 112 kbps).…”
Section: Quality Evaluation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The speech signal samples were processed in 5 different bitrates, namely: 8 kbps, 16 kbps, 24 kbps, 32 kbps, and 48 kbps. Previous studies concerning delivering speech audio signals showed that a bitrate of 48 kbps-64 kbps enables to deliver high-quality commercial services [6]- [8]. Additional information on speech signal processing may be found in [9].…”
Section: A Signal Samplesmentioning
confidence: 99%